Improving Students Vocabulary Mastery By Using Fly Swatter Game At The Seventh Grade Students Of SMP Negeri 2 Kulo - Syahrir L.; Andi Sadapotto; Pujiana Anwar; Sam Hermansyah (Prodi Pendidikan Bahasa Inggris, FKIP, LP3M Universitas Muhammadiyah Sidenreng Rappang, 2022)
The Objective of the research was to find out whether or not the fly swatter game improves the vocabulary mastery of seventh-grade students at SMP Negeri 2 Kulo. The method of investigation used in this study was the pre-experimental method with one group pre-test and post-test design. The population was the seventh grade students of SMPN 2 Kulo. The sum number of the population was 60 students consisting of three classes and one class (VII.1)was taken as a sample by using the purposive sampling technique, the sum number of thesample was 20. The instrument used in this research was to treat the group. The results of this study revealed that the pre-test received a mean score of 52,00, while the post-test received a mean score of 52,00. (78,55). The p-value (0.000) was lower than the level of significance (alpha = 0.05), indicating that the p-value (0.000) was lower than the level of significance. This means that H1 was accepted. The research concluded that teaching at the seventh-grade students of SMP Negeri 2 Kulo interested to learn vocabulary mastery by using fly swattergame.